Ekologi traumatik: Kekerasan lingkungan dan luka ekologis dalam novel Jejak Balak - Risnawati, Risnawati; Saryono, Djoko; Sulistyorini, Dwi; Laili, Hidayatul (Universitas Mulawarman, 2026)
Forest destruction and ecological violence in the novel Jejak Balak not only impact nature, but also cause psychological and social wounds for the community. This study aims to reveal the forms of ecological trauma represented in the novel through an ecocritical approach with the concept of traumatic ecology from Buell, Nixon, Rigby, Cunsolo, and Woolbright. The analysis was conducted descriptively qualitatively by examining narratives, dialogues, and descriptions that contain traces of ecological wounds. The research findings show seven forms of trauma: physical trauma due to deforestation, collective trauma in the form of mass fear, mythological-ecological trauma through the figure of the inyiak as a forest guardian, trauma of ecological violence seen in repressive actions by officials, moral trauma due to the ethical dilemma between nature conservation and violence, trauma of loss of place when the forest turns into a foreign space, and existential trauma related to the uncertainty of the ecological future. This study confirms that ecological damage produces multidimensional wounds that span from the body, living space, to the cultural consciousness of the community.